2010
DOI: 10.1007/s10895-010-0702-5
|View full text |Cite
|
Sign up to set email alerts
|

A Sandwiched Biological Fluorescent Probe for the Diagnosis of Human Ovarian Tumor Based on TiO2 Nanoparticles

Abstract: In this paper, we report a novel biological fluorescent probe for the diagnosis of human ovarian tumor based on sandwiched TiO(2) nanoparticles. The fluorescence nanoparticles consist of a fluorescent molecule, tetramethyl rhodamine isothiocyanate (TRITC), sandwiched between titanium dioxide (TiO(2)) nanoparticles and nano-gold via reacting with each other. The antibodies HER2, labeled on the surface of the biofluorescence nanoparticles, have granted nanoparticles the privilege of aiming at peculiar tumor anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…The knowledge of nanoparticles (NPs) and their potential application in the field of biomedicine as drug delivery [1,2], therapeutic [3][4][5], and diagnostic platforms and imaging devices [6] have improved significantly over recent years. While particles of different materials and sizes have been studied in detail, only a limited numbers of studies on ultra-small NPs, with sizes of less than 5 nm, have been reported [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The knowledge of nanoparticles (NPs) and their potential application in the field of biomedicine as drug delivery [1,2], therapeutic [3][4][5], and diagnostic platforms and imaging devices [6] have improved significantly over recent years. While particles of different materials and sizes have been studied in detail, only a limited numbers of studies on ultra-small NPs, with sizes of less than 5 nm, have been reported [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Titanium dioxide (TiO 2 ) [26] has been studied extensively in recent years due to its many potential applications [27,28] , in destroying contaminants from air and water [29][30][31] , antimicrobial nanomaterials [32][33][34][35] , in photo-electrical cells [36][37][38] , water splitting [39][40][41][42] , gas sensors [43] , and cancer therapy applications [44][45][46][47] .…”
Section: Introductionmentioning
confidence: 99%